2021
DOI: 10.1021/acs.cgd.1c00457
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Polymorphic Phases of a Mononuclear Spin-Crossover Fe(II) Complex with Significant Coligand Effect

Abstract: Polymorphism is known to show a significant effect on the crystal packing structures and physical properties of molecular complexes. On the basis of our previous works on the spin-crossover (SCO) complex [Fe­(tpa)­(NCS)2] (tpa = tris­(2-pyridylmethyl)­amine), we have prepared the analogous complex [Fe­(tpa)­(NCSe)2] using a NCSe– coligand and obtained a series of crystalline polymorphs, namely SeI–SeIV, respectively, by controlled synthetic processes. Single-crystal X-ray diffraction studies reveal that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…To better understand how different substrates can affect the functionality of SCO complexes, careful attention to other parameters that can potentially perturb SCO molecules should be considered. These include ligand types, film thickness, thin film fabrication method, surface properties of the substrates, and the probing methods used [91,[129][130][131][132][133][134][135][136][137][138]. 1500 nm thick [Fe(Htrz) 2 (trz)](BF 4 )] thin films on PVDF-TrFE polymer were fabricated as bilayer samples to be used potentially in MEMS devices [128].…”
Section: Other Parameters That Influence the Spin State Switchingmentioning
confidence: 99%
“…To better understand how different substrates can affect the functionality of SCO complexes, careful attention to other parameters that can potentially perturb SCO molecules should be considered. These include ligand types, film thickness, thin film fabrication method, surface properties of the substrates, and the probing methods used [91,[129][130][131][132][133][134][135][136][137][138]. 1500 nm thick [Fe(Htrz) 2 (trz)](BF 4 )] thin films on PVDF-TrFE polymer were fabricated as bilayer samples to be used potentially in MEMS devices [128].…”
Section: Other Parameters That Influence the Spin State Switchingmentioning
confidence: 99%
“…The switch ability and memory conduction of functional molecular materials are of great significance for molecular electronic devices involving switches, information storage, , and sensors. , Spin-crossover (SCO) complexes as a kind of controllable functional molecular material have been widely concerned due to their properties that can switch between the high-spin (HS) and the low-spin (LS) states in response to external stimuli such as temperature, light, and pressure. Since Cambi and Szegö reported the first SCO complex in 1931, there has been a long investigation of this class of complexes with unique properties. To date, a great deal of novel and interesting SCO complexes have been synthesized and characterized. , To achieve the practical or potential applications in molecular devices, predicting and regulating the occurrence of SCO properties has always been the focus of current research. …”
Section: Introductionmentioning
confidence: 99%
“…When both energies are comparable, the SCO phenomenon can easily occur with external stimuli such as temperature, pressure, light, electric field, guest molecules, etc. Since the structure of the organic ligand directly determines the ligand field strength, regulating SCO behavior by modifying the organic ligand, which directly links the SCO metal center, is a common research method that has been extensively studied. However, the effect of such a direct modification of ligands on SCO properties is complicated and is usually attributed to steric or electronic effects. Some earlier reports have also pointed out the differences between σ-donating and π-accepting properties of ligands to explain the complexity of the electronic effects of substituents on the SCO properties. , Therefore, the regulation of SCO properties by directly modifying the ligand, which directly links the SCO metal center is often unpredictable. To date, although there have been some reports on the regulation of the SCO properties of complexes, it remains a great challenge to fine-tune the properties of SCO, especially the spin transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Spin crossover in the solid state can be affected by many parameters such as crystallinity, crystal mosaicity, anion conformation, etc . In the end, the spin transition for the very same material may be different if polymorphism occurs. While the quantity and quality of interactions between the SCO active sites, solvent molecules, and/or anions , is certainly key to control the cooperativity among the centers, real a priori prediction of the magnetochemical feedback is out of reach. , This remains a major challenge in the solid state, albeit ongoing efforts are being made to establish rules a posteriori and to develop rational strategies (crystal engineering). , On the other hand, recent studies in the solution phase for different compound series have shown that the spin transition curves can be selectively affected by either solvent tuning, alkyl chain length, or the Hammett substitutent parameter …”
Section: Introductionmentioning
confidence: 99%